Dietary intakes and anthropometric measures of Indigenous Australian women and their infants in the Gomeroi gaaynggal cohort. (27th June 2016) - Ashman, A. M.; Collins, C. E.; Weatherall, L. J.; Keogh, L.; Brown, L. J.; Rollo, M. E.; Smith, R.; Rae, K. M.
Abstract : Indigenous Australians continue to experience disparities in chronic diseases, many of which have nutrition-related trajectories. Optimal nutrition throughout the lifespan is protective for a number of adverse health outcomes, however little is known about current dietary intakes and related anthropometric outcomes of Indigenous women and their infants. Research is required to identify nutrition issues to target for health promotion activities. The Gomeroi gaaynggal programme is an ongoing, prospective cohort of pregnant Indigenous Australian women and their children. A cross-sectional examination of postnatal dietary intakes and anthropometric outcomes of mothers and children are reported. To date, 73 mother–child dyads have participated postpartum . Breastfeeding initiation was 85.9% and median (interquartile range) duration of any breastfeeding was 1.4 (0.5–4.0) months. Infants were introduced to solid foods at 5.0 months (4.0–6.0) and cow's milk at 12.0 (10.0–13.0) months. At 12 months postpartum, 66.7% of women were overweight or obese, 63.7% at 2 years. Compared with recommendations, reported median maternal nutrient intakes from 24-h recall were low in fibre, folate, iodine, calcium, potassium and vitamin D and high in proportions of energy from total and saturated fat. Limitations of this study include a small sample size and incomplete data for the cohort at each time point. Preliminary data from this ongoing cohort of Indigenous Australian women and children suggest that women may need support to optimize nutrient intakes and to attain a healthy body weight for themselves and their children.